(untitled) (Journal of Parents and Teachers, 2015)
In educating, both parents and teachers want to know more and more which ones are the ways to help children or pupils to develop as a person, as a complete person, benefiting themselves on Creation. Nowadays there are many opportunities to achieve this goal, but it’s needed to think about some abuses than can possibly install in the subconscious, coming from consumer society, technological society and well-being society. In this article we expose a reflection on the risk of this issues for personal identity development